Compression‐compression fatigue performance of aluminium matrix composite foams reinforced by carbon nanotubes. Issue 4 (9th January 2020) - Yang, Xudong; Hu, Qi; Li, Weiting; Song, Haipeng; Zou, Tianchun; Zong, Rongrong; Sha, Junwei; He, Chunnian; Zhao, Naiqin
Abstract: The compression‐compression fatigue performance of carbon nanotube (CNT) reinforced aluminium matrix composite foams (AMCFs) were investigated. The ε ‐ N curves of AMCFs are composed of three stages (the elastic, strain hardening, and rapid accumulation stages), while the fatigue strain of AMCFs accumulates very rapidly in stage III compared with Al foams. The fatigue strength of AMCFs with CNT contents of 2.0, 2.5, and 3.0 wt% increases by 6%, 44%, and 102% than Al foams, respectively. Different from Al foams' deformation of layer‐by‐layer, the main failure modes of AMCFs are the brittle fracture and collapse of pores within significant shear deformation bands under fatigue loading. The uniform distribution of CNTs and good interfacial bonding of CNTs and Al matrix is the important factor for the improvement of fatigue properties of AMCFs.